2021
DOI: 10.1186/s12935-021-01764-8
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0010235 functions as an oncogenic drive in non-small cell lung cancer by modulating miR-433-3p/TIPRL axis

Abstract: Background Non-small cell lung cancer (NSCLC) is a threat to human health. Circular RNAs (circRNAs) have been proved to function in NSCLC development. In this study, the role of circRNA hsa_circ_0010235 in NSCLC progression and the possible molecular mechanism were explored. Methods Expression of hsa_circ_0010235, miRNA (miR)-433-3p and TOR signaling pathway regulator-like (TIPRL) was examined by quantitative real-time PCR (qRT-PCR). Cell viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…17,[38][39][40][41] CircRNAs indirectly increase the expression levels of downstream target gene mRNAs and proteins by adsorbing miRNAs and participate in the occurrence and development of tumors. [42][43][44][45][46] Xu et al found that hsa-circ-000984 was mainly concentrated in the cytoplasm and identified the downstream target as miR-106b, indicating that hsacirc-000984 can act as a ceRNA by competitively binding miR-106b, increasing the expression of cyclin-dependent kinase 6 (CDK6) and participating in the proliferation and metastasis of CRC. It is worth noting that the high expression of hsa-circ-000984 is significantly related to TNM staging and the cell cycle.…”
Section: Crcmentioning
confidence: 99%
“…17,[38][39][40][41] CircRNAs indirectly increase the expression levels of downstream target gene mRNAs and proteins by adsorbing miRNAs and participate in the occurrence and development of tumors. [42][43][44][45][46] Xu et al found that hsa-circ-000984 was mainly concentrated in the cytoplasm and identified the downstream target as miR-106b, indicating that hsacirc-000984 can act as a ceRNA by competitively binding miR-106b, increasing the expression of cyclin-dependent kinase 6 (CDK6) and participating in the proliferation and metastasis of CRC. It is worth noting that the high expression of hsa-circ-000984 is significantly related to TNM staging and the cell cycle.…”
Section: Crcmentioning
confidence: 99%
“…Increasing evidence has shown that many circRNAs (such as circ_010763, circ_001010, and circ_0078767) can affect lung cancer progression 22–24 . As a circRNA, circ_0010235 has previously been found to be overexpressed in lung cancer cells and tissues, and depletion of circ_0010235 limited the proliferation and autophagy and contributed to apoptosis in lung cancer cell lines through regulation of miR‐433‐3p/TIPRL axis 13 . In line with this research, an increase of circ_0010235 expression was also found in lung cancer cells and tissues, and circ_0010235 silencing repressed lung cancers cell growth and invasion and induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that circ_0010235 acted as a tumor promoter in lung cancer. 13 However, the function of circ_0010235 in lung cancer immune response has not been reported, and its mechanism has not yet been fully established.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Zhang et al manifested that hsa_circ_0010235 downregulation facilitated NSCLC cell apoptosis and repressed NSCLC cell autophagy and proliferation by decreasing TIPRL expression via releasing miR‐433‐3p. 17 Also, circMED13L_012 elevated MAPK8 expression through adsorbing miR‐433‐3p, thus elevating cell chemoresistance and promoting metastasis and invasion in NSCLC. 16 Accordingly, we inferred that circ_0008037 regulated NSCLC cell proliferation, migration, invasion, and the Warburg effect through adsorbing miR‐433‐3p.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Recent studies have exposed the inhibitory effect of miR‐433‐3p on NSCLC progression. 15 , 16 , 17 However, the dysregulation of miR‐433‐3p in NSCLC has not been fully explained.…”
Section: Introductionmentioning
confidence: 99%